Pre-procedural peripheral endothelial function is associated with increased serum creatinine following percutaneous coronary procedure in stable patients with a preserved estimated glomerular filtration rate. Issue 5 (November 2017) - Sumida, Hitoshi; Matsuzawa, Yasushi; Sugiyama, Seigo; Sugamura, Koichi; Nozaki, Toshimitsu; Akiyama, Eiichi; Ohba, Keisuke; Konishi, Masaaki; Matsubara, Junichi; Fujisue, Koichiro; Maeda, Hirofumi; Kurokawa, Hirofumi; et al.
Abstract: Background: Worsening renal function, indicated by increased serum creatinine (SCr), is a common complication of percutaneous coronary procedures. Risk factors for increased SCr overlap with coronary risk factors involved in endothelial dysfunction. We hypothesized that endothelial dysfunction, measured using the reactive hyperemia peripheral arterial tonometry index (RHI), can predict periprocedure-increased SCr. Methods: RHI was assessed before elective coronary procedures in 316 consecutive stable patients with a preserved estimated glomerular filtration rate (eGFR, >60 mL/min/1.73 m 2 ). SCr was measured before and 2 days after procedures. Results: There was no significant correlation between natural logarithmic transformations of RHI (Ln-RHI) and basal Ln-eGFR. Periprocedure increase in SCr was observed in 148 (47%) patients. The increased SCr group had significantly lower Ln-RHI [0.48 (0.36, 0.62) vs. 0.59 (0.49, 0.76), p  < 0.001]. Multivariate linear regression analysis identified body mass index (BMI) ( β  = 0.148, p  = 0.005) and Ln-RHI ( β  = − 0.365, p  < 0.001) as significant determinants of percent changes in SCr. Multivariate logistic regression analysis identified Ln-RHI (per 0.1) [odds ratio (OR) 0.672, 95% confidence interval (95% CI) 0.586–0.722; p  < 0.001], Ln-B-type natriuretic peptide (OR: 1.484, 95% CI: 1.130–1.974; p  = 0.004), current smoking (OR: 2.563, 95% CI: 1.379–4.763, p  = 0.003), BMI (OR: 1.113, 95% CI: 1.031–1.203; p  = 0.007), coronary intervention (OR: 1.736, 95% CI: 1.036–2.909; p  = 0.036), and Ln-hemoglobin A1c (OR: 6.728, 95% CI: 1.093–41.392, p  = 0.040) as independent determinants of increased SCr. Receiver-operating characteristics curve analysis showed that Ln-RHI correlated significantly with increased SCr (area under the curve, 0.684, 95% CI: 0.626–0.742, p  < 0.001). The optimum cut-off point of Ln-RHI for the periprocedure increased SCr was 0.545. Conclusions: Pre-procedure measurement of endothelial function by RHI is an effective strategy to assess the patient's risk conditions for worsening renal function after percutaneous coronary procedures.